An end-user tool for supporting frequent multisource web search workflows - Tacuri, Alex (2025)
Current web browser support for search tasks often lead to tedious and time-consuming processes especially when information needs span across various domains and when these tasks are done frequently. This paper addresses this challenge by proposing an approach that empowers end users to seamlessly conduct complex web search workflows. By prioritizing end-user programming and controllability, our approach enables users to customize and automate their search processes according to individual preferences and needs. We emphasize the importance of maintaining user control and awareness of information sources. Through our approach, we aim to enhance user experience and efficiency in accessing information across diverse online platforms.